Legal Education on Domestic Violence Prevention as an Effort to Raise Legal Awareness in the Community of Ngaresrejo Village, Sidoarjo Regency - Haniyah; Yayu Sriwahyuni Hamzah; Yayuk Sugiarti; Budi Handayani; Cyntia Varashena Zabella; Wiati Samawati (LP2M of Institute for Research and Community Services - UIN Walisongo, 2026)
Domestic violence remains a persistent social problem that negatively affects the physical, psychological, and social well-being of victims. In Ngaresrejo Village, Sidoarjo Regency, preliminary observations indicated that community members had limited knowledge regarding the forms of domestic violence, victims’ legal rights, and available legal protection mechanisms. This condition highlights the need for community-based legal education as a preventive strategy to strengthen public awareness and encourage early intervention in domestic violence cases. This community service program aimed to enhance legal awareness and strengthen the community’s capacity to prevent domestic violence through a participatory legal education approach grounded in community empowerment principles. The program involved 30 participants, including homemakers, community leaders, and youth representatives. Activities included legal counseling, interactive discussions, and case-based learning, designed to encourage active community participation and critical reflection on domestic violence issues. Program effectiveness was evaluated using pre-test and post-test assessments. The results demonstrated a substantial improvement in participants’ understanding of domestic violence and legal protection mechanisms. Before the intervention, 66.7% of participants were categorized as having a low level of understanding, and 33.3% a moderate level. Following the program, 90% of participants achieved a high level of understanding. Beyond increasing legal knowledge, the activity also fostered greater community awareness of the importance of preventing domestic violence. It strengthened participants’ readiness to contribute to creating a safer family and social environment. These findings suggest that participatory legal education is an effective community empowerment strategy for improving legal awareness and supporting sustainable domestic violence prevention efforts at the community level.